Pervasive computing 9th international conference, pervasive 2011, San Francisco, USA, June 12-15, 2011: proceedings - Lyons, Kent (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 9th International Conference on Pervasive Computing, Pervasive 2011, held in San Francisco, USA, in June 2011. The 19 revised full papers and three short papers presented were carefully reviewed and selected from 93 submissions. The contributions are grouped into the following topical sections: practices with smartphones; sensing at home, sensing at work; predicting the future; location sensing; augmenting mobile phone use; pervasive computing in the public arena; public displays; hands on with sensing; sensing on the body.